Transformation: Library Services Traditional And Modern - Sofiyani, Zulfatun; jamil, awalludin; Ayu, Christasya Rasmaning (LIBTECH: LIBRARY AND INFORMATION SCIENCE JOURNAL, 2024)
The development of information and communication technology has changed library services from traditional to modern. In the current era, digital libraries have utilized technologies such as barcoding to improve operational efficiency, speed up the process of borrowing, returning and collection data collection. Objective: to understand the differences between traditional and modern library services and the skills librarians need to manage these changes. Methods: Analysis, synthesis and comparison methods were used to understand library development services from various aspects. This involves historical, social, cultural and technological analysis. Results: that digital libraries are not just about collecting materials online, but also providing services, maintaining traditions, and providing access to accurate information. Comparison of traditional and modern library services shows significant changes in terms of functions, technologies used, and service efficiency. Recommendation: Librarians should develop new skills and utilize technology to improve library services.  Keywords: Transformation, Library Services, Information and Communication Technology.